2013
DOI: 10.1111/fwb.12169
|View full text |Cite
|
Sign up to set email alerts
|

Fish recruitment in rivers with modified discharge depends on the interacting effects of flow and thermal regimes

Abstract: Summary Alteration of flow and thermal regimes is a key consequence of human use of river and floodplain ecosystems, and these impacts result from a range of interacting ecological mechanisms. Environmental flow regimes are a management strategy to restore or maintain ecologically important aspects of river hydrology. However, inadequate understanding of the processes that determine the effects of flow on population dynamics of biota hinders the maximum benefits of environmental flows. Spawning and recruitme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
69
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(72 citation statements)
references
References 71 publications
2
69
0
1
Order By: Relevance
“…The strength of associations between abiotic indices and macroinvertebrate community responses typically improved when seasonal models were considered, with no thermal indices comprising the most highly correlated models. This is in contrast to research highlighting that comparable ecological variance could be explained by flow and stream temperature variability within some regulated systems (Jackson et al, ; Rolls et al, ). This study found that hydrological indices relating to the timing of extreme flows were of high ecological significance across both regulated and non‐regulated sites.…”
Section: Discussionmentioning
confidence: 99%
“…The strength of associations between abiotic indices and macroinvertebrate community responses typically improved when seasonal models were considered, with no thermal indices comprising the most highly correlated models. This is in contrast to research highlighting that comparable ecological variance could be explained by flow and stream temperature variability within some regulated systems (Jackson et al, ; Rolls et al, ). This study found that hydrological indices relating to the timing of extreme flows were of high ecological significance across both regulated and non‐regulated sites.…”
Section: Discussionmentioning
confidence: 99%
“…YOY abundance is regulated by abiotic and biotic conditions in freshwater fishes. Spawning success, egg survival and post‐hatching survival have been linked to water temperature (Warren et al ., ; Rolls et al ., ) and stream flow (Fausch et al ., ; Smith, Odenkirk & Reeser, ; Dutterer et al ., ). This indicates that climate change is a mechanism that will likely affect YOY abundance dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Temporal variations in environmental forces often result in time‐lagged ecological responses and the effects persist for certain periods of time (the so‐called antecedent effect, hysteresis, and ecological memory). Such antecedent effects have been observed in freshwaters and other realms at all ecological scales: physiological and behavioral changes of organisms (Tonkin et al , Amorim et al ), population dynamics (Magalhães et al , Rolls et al , George et al ), distributional ranges of species, and resistance and resilience at the community and ecosystem levels (Kinzig et al , Tockner et al ). The inclusion of antecedent effects at appropriate time scales in models generally better explains variations in ecological responses (Ogle et al ).…”
mentioning
confidence: 99%